Children show neural sensitivity to facial trustworthiness as measured by fast periodic visual stimulation. (10th February 2023) - Siddique, Saba; Sutherland, Clare A.M.; Jeffery, Linda; Swe, Derek; Gwinn, O Scott; Palermo, Romina
Abstract: Adults exhibit neural responses over the visual occipito-temporal area in response to faces that vary in how trustworthy they appear. However, it is not yet known when a mature pattern of neural sensitivity can be seen in children. Using a fast periodic visual stimulation (FPVS) paradigm, face images were presented to 8-to-9-year-old children (an age group which shows development of trust impressions; N = 31) and adult (N = 33) participants at a rate of 6 Hz (6 face images per second). Within this sequence, an 'oddball' face differing in the level of facial trustworthiness compared to the other faces, was presented at a rate of 1 Hz (once per second). Children were sensitive to variations in facial trustworthiness, showing reliable and significant neural responses at 1 Hz in the absence of instructions to respond to facial trustworthiness. Additionally, the magnitude of children's and adults' neural responses was similar, with strong Bayesian evidence that implicit neural responses to facial trustworthiness did not differ across the groups, and therefore, that visual sensitivity to differences in facial trustworthiness can show mature patterns by this age. Thus, nine or less years of social experience, perceptual and/or cognitive development may be sufficient for adult-like neural sensitivity to facial trustworthiness to emerge. We also validate the use of the FPVS methodology to examine children's implicit face-based trust processing for the first time, which is especially valuable in developmental research because this paradigm requires no explicit instructions or responses from participants. Highlights: Children aged eight to nine years show reliable and significant neural responses to variations in facial trustworthiness. Neural responses were observed in the absence of explicit instructions to attend to facial trustworthiness, indicating a degree of automaticity. Strong Bayesian support was found for children's and adults' neural responses being equal in magnitude. Fewer than nine years of development may be sufficient for adult-like neural sensitivity to facial trustworthiness to emerge.